Two new compounds from the green peel of Juglans mandshurica. Issue 11 (2nd November 2017) - Li, Jing; Xu, Kang-Ping; Zou, Zhen-Xing; Zou, Hui; Long, Hong-Ping; Tan, Lei-Hong; Liu, Rui-Huan; Wang, Yi-Kun; Xu, Ping-Sheng; Tan, Gui-Shan
Abstract: A new cyclic diarylheptanoid (1 ) and a new flavone glucoside (2 ), along with seven known compounds, were isolated from the green peel of Juglans mandshurica . Their structures were elucidated based on extensive spectroscopic analyses. Moreover, the cytotoxicity against NCI-H460, A549, and K562 cancer cells of compounds1–6 was evaluated. The results showed that compound3 exhibited moderate inhibitory potency against the growth of three cell lines. Abstract :